Creativity and entrepreneur knowledge to increase entrepreneurial intent among vocational school students - Muhammad Kris Yuan Hidayatulloh; Hilyah Ashoumi (Intelektual Pustaka Media Utama, 2022)
One way to overcome the problem of unemployment is to change the mindset that in meeting the needs of life, one does not have to work as an employee or employee, but is able to play a role as a business pioneer. This study aims to find out the contribution level of entrepreneurship education and creativity taking into account factors that support entrepreneurs’ intents. This type of investigation was ex post facto with a quota sampling technique of 76 vocational high school students. The data collection was done through tests to measure entrepreneurial knowledge and instruments to measure entrepreneurial intentions. The data analysis technique employed a regression test to determine the relationship and the magnitude of the influence between variables. The study has found that there is a positive correlation between entrepreneurial education and students’ intent in entrepreneurship. The contribution of change in entrepreneurship education partly to intent in entrepreneurship was 32.60%. There is a positive contribution to creativity in students’ intents in entrepreneurship. The contribution to allow for creative change in entrepreneurial intent is partially 18.40%. There is a positive contribution between entrepreneurship education and creativity in students’ intent in entrepreneurship. Other supporting factors are self-efficacy and locus of control.